Review of the genus Schizoturanius Verhoeff, 1931, with the description of a new species from the Altais, Asian Russia (Diplopoda: Polydesmida: Polydesmidae) - Nefediev, Pavel S. (Zootaxa, 2022)
Schizoturanius krugovae sp. nov. is described from the Tigirek State Nature Reserve and its immediate adjacent areas in the Altai Krai, southwestern Siberia, Russia. The new species is diagnosed and described using scanning electron microscopy, compound microscopy, and genetic data. The list of all accepted species of the genus Schizoturanius, notes on their distribution and other short remarks are given. A brief phylogenetic analysis for three Schizoturanius species is provided, and barcoding information (a fragment of the mitochondrial COI nucleotide sequence) of the new species has been deposited in GenBank. A key is presented to all nine species of the genus, and their distribution is mapped.